Nanoplatforms: Theranostic Nanoplatforms for MRSA Detection and Destruction from Whole Blood (Part. Part. Syst. Charact. 3/2014). (March 2014) - Fan, Zhen; Khan, Sadia Afrin; Dai, Xuemei; Tchouwou, Christine; Lu, Yuefeng; Ray, Paresh Chandra
<x xml:space="preserve">Abstract</x> Paresh C. Ray and co‐workers report on page 357 the development of multifunctional theranostic nanoplatforms, which is capable of targeted detection and destruction of methicillin‐resistant Staphylococcus aureus (MRSA) from whole blood. The image shows that the theranostic nanoplatform has a great potential for simultaneous separation, imaging and multimodal photodestruction of MRSA in the blood sample. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>